a) \frac{3}{2 \sqrt{7} } = \frac{3 \times \sqrt{7} }{2 \times \sqrt{7 \times }\sqrt{7} } = \frac{3}{2 \times 7} = \frac{3}{14}a)
2
7
3
=
2×
7×
7
3×
7
=
2×7
3
=
14
3
\begin{gathered}b) \frac{9}{7 + 4 \sqrt{3} } = \frac{9 \times (7 - 4 \sqrt{3} )}{(7 + 4 \sqrt{3} ) \times (7 - 4 \sqrt{3} )} = \frac{63 - 36 \sqrt{3} }{ {7}^{2} -{ (4 \sqrt{3}) }^{2} } = \\ = \frac{63 - 36 \sqrt{3} }{49 - 16 \times 3} = \frac{63 - 36 \sqrt{3} }{49 - 48} = \frac{63 - 36 \sqrt{3} }{1} = 63 - 36 \sqrt{3}\end{gathered}
b)
7+4
3
9
=
(7+4
3
)×(7−4
3
)
9×(7−4
3
)
=
7
2
−(4
3
)
2
63−36
3
=
=
49−16×3
63−36
3
=
49−48
63−36
3
=
1
63−36
3
=63−36
3
-32,7×0,1x+6,3=0
-3,27x=-6,3
x=-6,3÷(-3,27)
x=1,9266055046
проверка:
-32,7×0,1×1,9266055046+6,3=0